Apolipoprotein AI transgene corrects apolipoprotein E deficiency-induced atherosclerosis in mice. - Pászty, C (1994)
Apolipoprotein E (apo E)-deficient mice are severely hypercholesterolemic and develop advanced atheromas independent of diet. The C57BL/6 strain differs from most inbred strains by having lower HDL concentrations and a high risk of developing early atherosclerotic lesions when fed an atherogenic diet. The relative HDL deficiency and atherosclerosis susceptibility of the C57BL/6 strain are corrected with the expression of a human apolipoprotein AI (apo AI) transgene in this genetic background. To examine if increases in apo AI and HDL are also effective in minimizing apo E deficiency--induced atherosclerosis, we introduced the human apo AI transgene into the hypercholesterolemic apo E knockout background. Similar elevations of total plasma cholesterol occurred in both the apo E knockout and apo E knockout mice also expressing the human apo AI transgene. The latter animals, however, also showed a two- to threefold increase in HDL and a sixfold decrease in susceptibility to atherosclerosis. This study demonstrates that elevating the concentration of apo AI reduces atherosclerosis in apo E deficient-mice and suggests that elevation of apo AI and HDL may prove to be a useful approach for treating unrelated causes of heightened atherosclerosis susceptibility.